Environment and sustainability. - (:unkn) unknown (Lang, 2019)
The fact that environmental issues, which cause a significant externality within global goods, have gained a global dimension, necessitated more concrete steps for challenging with environmental issues. At this point, efforts to reduce environmental issues and protect the environment have been on the axis of sustainability. This book contains theoretical and empirical researches written by academicians and researches in the field of environment and sustainability. In the contributions, the macro dimensions of environmental pollution such as economic growth, health sector and technological development are examined. In addition to these, the contributors deal with micro dimensions such as consumption, marketing, accounting and firm behavior both in theory and empirically.
Keywords: Wirtschaftsentwicklung; Wirtschaftswachstum; Wirtschaftstheorie; Nachhaltigkeit; Nachhaltige Entwicklung; Mikroökonomie; Makroökonomie; Umweltökonomie; Umweltwirkung; Klimawandel; Gütermarkt